Nitric oxide and reactive species are modulated in the polyphenol‐induced ductus arteriosus constriction in pregnant sheep. (22nd August 2014) - Bubols, Guilherme B.; Zielinsky, Paulo; Piccoli, Antônio L.; Nicoloso, Luiz H.; Vian, Izabele; Moro, Angela M.; Charão, Mariele F.; Brucker, Natália; Bulcão, Rachel P.; Nascimento, Sabrina N.; Baierle, Marília; Alievi, Marcelo M.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Polyphenol‐rich foods have been associated to premature ductal constriction when consumed in the third trimester of pregnancy. What does this study add? Polyphenols revealed to induce vasoconstriction of the ductus arteriosus by inhibiting nitric oxide vasodilatation. Consumption of polyphenol‐rich foods in late pregnancy showed partial antioxidant effect by contributing to reduce lipid peroxidation. In contrast, NO‐mediated ductal vasoconstriction could also be associated to oxidative damage to proteins.